Fractional 1, 927 nm Thulium Laser Plus Photodynamic Therapy Compared and Combined for Photodamaged Décolleté Skin: A Side‐by‐Side Randomized Controlled Trial. Issue 1 (1st December 2019) - Hendel, Kristoffer; Mogensen, Mette; Wenande, Emily; Dierickx, Christine; Haedersdal, Merete; Togsverd‐Bo, Katrine
Abstract : Background and Objectives: Décolleté photodamage is a common condition typically treated with light and energy‐based devices. This study investigated the efficacy and safety of a fractional 1, 927 nm thulium laser (TL) alone and combined with photodynamic therapy (PDT). Study Design/Materials and Methods: In a 12‐week follow‐up study, participant décolletés were divided into four treatment areas and randomized to receive a single treatment with field‐directed TL, PDT, combination TL‐PDT, or lesion‐directed curettage control. All actinic keratoses (AKs) underwent lesion‐directed curettage before randomization. TL was delivered at 20 mJ/mb, 500 mJ/cm 2 fluence, 5 W, and 8 ( n  = 6 pts.) or 16 ( n  = 6 pts.) passes. PDT was performed with 16% methyl aminolevulinate (MAL) creme incubated for 3 h, followed by red light‐emitting diode light at 37 J/cm 2 . Outcome measures included clinical assessment of overall photodamage and specific subcomponents, assisted by optical coherence tomography (OCT) imaging. Results: Twelve women with moderate to severe photodamage on the décolleté and a cumulative total of 184 thin grade I AKs were included. Field‐directed treatments TL and combination TL‐PDT equally improved the overall photodamage, mottled pigmentation, and rhytides compared with lesion‐directed control ( P  < 0.05). The skin texture improved by TL alone and was further improved by combining TL and PDT ( P  < 0.05). Median AK complete responses were similar for field‐directed interventions TL‐PDT (100%), TL (90%), PDT (82%), and lesion‐directed curettage control (52%) ( P  = 0.464). Patients presented with mild local skin responses, slightly more pronounced when combining TL with PDT versus individual treatments ( P  < 0.05). No scarring or adverse events were observed. Conclusions: The 1, 927 nm fractional thulium laser is an effective, tolerable, and safe field‐directed treatment for décolleté photodamage. Provided alone, TL proved to be as effective as combined TL‐PDT for overall photodamage, while a greater improvement in skin texture was achieved using TL and PDT in combination. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.